ART THERAPY TO IMPROVE THE WELL-BEING OF THE ELDERLY AT EMBUN KEHIDUPAN BANGSA NATION - Icha Herawati; Kania Kusuma Wardani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Living as an elderly person is difficult, especially when you live far from your family. Many changes and declining abilities cause elderly people to experience many declines in function in life. So in this situation, a special approach is needed for the elderly to maintain psychological well-being. The elderly who are residents at the Embun Life Nation Foundation are elderly people who need to be given special attention regarding their well-being. This activity aims to help the elderly residents of the Embun Life Nation Foundation to improve their well-being. The activities were Art therapy, live trapi review, and icebreaking. In the activities, elderly people who were active and having fun participating in the activities were seen. The seniors admitted that they were happy and pleased to take part in this activity and they hoped that this activity could be carried out sustainably.